Type D Personality and Alexithymia: Common Characteristics of Two Different Constructs. Implications for Research and Clinical Practice - Epifanio, Maria S.; Ingoglia, Sonia; Alfano, Pietro; Lo Coco, Gianluca; La Grutta, Sabina (Frontiers in Psychology, 2018)
In the last few decades, particular attention has been paid to the role of personality specific traits that can affect the loss of health, i.e., Type D personality and Alexithymia. They have been conceptualized in a different period, this means that they are different both for their theoretical positions and their empirical studies. Some authors have speculated that there is a potential conceptual overlap between Type D personality and alexithymia constructs but there is a shortcoming in the literature. The aim of the study was to examine the potential overlap between the constructs of type D personality and alexithymia, replicating previous two studies, to extend these findings to Italian population. The participants were 247 Italian adults (males = 43%), recruited in primary health care practices of Palermo. All participants did not have chronic diseases during tests administration. They ranged in age from 35 to 69 years old (M = 52.34 years, SD = 9.76). Participants were administered Type D Personality Scale (DS-14) and Toronto Alexithymia Scale (TAS-20). A series of confirmatory factor analyses was performed to evaluate the factorial structure underlying the TAS-20 and DS-14 items. Globally results showed that alexithymia and type D personality are distinct constructs, but they are also strictly positively related with each other. Negative affectivity (NA) was highly correlated with Difficulties in identifying feelings and Difficulties in describing feelings, while Social inhibition (SI) was highly correlated with Difficulties in describing feelings. These results are consistent with those of other studies conducted in this area. Future research should consider evaluating the relationship between a deficit of affect regulation and type D personality to improve the effectiveness of interventions of health cure.